Overtraining - Wilmore, J. H.; Costill, D. L.
"Numerous investigators have used assorted physiological measurements in an effort to objectively diagnose overtraining in its early stages to prevent its occurrence. Unfortunately, none has proven totally effective. It is often difficult to differentiate whether the measurements are abnormal and related to overtraining, or simply the normal physiological responses to heavy training. Measurements of blood enzyme levels have been used to diagnose overtraining with only limited success. Such enzymes as CPK (creatine phosphokinase), LDH (lactate dehydrogenase), and SGOT (serum glutamic transaminase) are important in muscle energy production . . . . . and muscle damage. . . . Although the effects of muscle damage on performance are not fully understood, experts generally agree that they may be, in part, responsible for the localized muscle pain, tenderness, and swelling associated with muscle soreness. There is, however, no evidence that this condition is linked to the symptoms of overtraining. . . . . blood enzyme levels do not appear to be a valid indicator of overtraining." (p. 196) ". white blood cell count tends to rise during exhaustive exercise . . . it is not clear whether this change is a sign of overstress or simply a normal reaction to intense training." (p. 196) "It has also been suggested that unusually high resting, blood lactate concentrations may be a sign of overstress. Many swimmers have been found to have high resting blood lactate concentrations when they are swimming poorly, and have normal concentrations when they are swimming well. Recent studies by Maglischo (1987), however, have failed to support this idea." (p. 197) [Maglischo reference not included in the chapter reference list.] ". no single physiological measurement has proven 100 percent effective. Since performance is the most dramatic indicator of overtraining, it is not surprising to find that overtraining has a dramatic effect on the energy demands for a standard, submaximal exercise bout. When runners show symptoms of overtraining, their heart rates and oxygen consumption during the runs are significantly higher." (p. 197) ". overtrained runners do not lose their conditioning, but they may demonstrate a deterioration in running form. . . .overtraining may cause some local muscular fatigue through selective glycogen depletion, forcing runners to alter their mechanics to achieve the same pace." (p. 198) "We are inclined to feel that athletes recover faster when they rest completely for three to five days, or engage in some other form of low-intensity exercise." (p. 198) "Unless the athlete consumes extra quantities of carbohydrate-rich foods during these periods [of heavy training], muscle and liver glycogen reserves may be depleted." (p. 199) Implication. These arguments give support to the use of the economy profile as a means of determining energy delivery breakdown or inefficiency as a symptom of overtraining.